2021
DOI: 10.1016/j.euros.2021.05.006
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cytoreductive Radical Prostatectomy in the Treatment of Newly Diagnosed Low-volume Metastatic Prostate Cancer. Results from the Local Treatment of Metastatic Prostate Cancer (LoMP) Registry

Abstract: Background Radiotherapy to the prostate (RTp) prolongs survival for patients with low-volume, newly diagnosed metastatic prostate cancer (ndmPC). Objective to evaluate whether cytoreductive radical prostatectomy (cRP) is equally beneficial as RTp in low-volume ndmPC. Design, setting, and participants A multicenter prospective registry was established in 2014 to observe patients with ndmPC. Eligible patients were offered cRP or RTp. For this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 27 publications
1
29
1
1
Order By: Relevance
“…In addition, a recently published prospective registry study, the Belgian LoMP trial, confirmed the equivalent efficacy of surgery and RT in omHSPC [9]. In this comparative study of 109 men treated with surgery, RT, or no local treatment, the locally treated group had a survival advantage over no local treatment.…”
mentioning
confidence: 53%
“…In addition, a recently published prospective registry study, the Belgian LoMP trial, confirmed the equivalent efficacy of surgery and RT in omHSPC [9]. In this comparative study of 109 men treated with surgery, RT, or no local treatment, the locally treated group had a survival advantage over no local treatment.…”
mentioning
confidence: 53%
“…3 B). Three studies assessed the OS of oligometastatic PCa, [ 7 , 12 , 13 ] and pooled data showed cytoreductive surgery did not significantly affect the OS (OR = 1.33, 95% CI 0.87–2.02, P = .19, Fig. 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…A phase 3 trial found that prostate-directed radiation can improve survival outcomes in patients with a low metastatic burden ( 26 ). Despite no hard evidence for the survival benefit of CRP in oligometastatic prostate cancer, several retrospective and prospective studies have suggested that CRP reduces the risk of clinical progression and improves long-term survival in patients with oligometastatic prostate cancer ( 3 6 , 13 ). Currently, PSA kinetics are commonly used to follow disease progression, but they cannot be utilized to predict the prognosis of omHSPC patients well because of inherent limitations ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies have reported that cytoreductive radical prostatectomy (CRP) reduces the risk of clinical progression and improves cancer-specific survival (CSS) ( 3 5 ). According to a recent prospective registry, CRP is able to improve CSS and overall survival (OS) in newly diagnosed low-volume metastatic prostate cancer patients ( 6 ). Despite improvements in diagnosis and treatment, omHSPC patients comprise a heterogeneous population of men with different outcomes who will ultimately develop castration-resistant cancer ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%